A feasibility study on non-invasive oxidative metabolism detection and acoustic assessment of human vocal cords by using optical technique - Lin, Tzu-Chieh (Sci Rep, 2017)
Voice disorder such as vocal fatigue is a common and complex multifaceted clinical problem that presents a significant impact on quality of life. In this study, the functional near-infrared diffuse optical technique (fNIRS-DOT) was proposed as a novel approach for human vocal cords oxidative metabolism detection and acoustic assessment simultaneously to provide a multidimensional assessment of voice disorder. A totally of 60 healthy subjects included 30 male and 30 female adults of age-matched were recruited and performed a vocal loading task to trigger a mild inflammation of the vocal cords in this study. In the results of oxidative metabolism, the vocal cords expressed hypoxia after vocal loading task in both male and female groups that could provide relevant information on the relationship between tissue oxygen consumption and supply for vocal cords diagnosis. Additionally, the results of optical acoustic assessment revealed the worse/changes voice quality after vocal loading task. Therefore, integration of non-invasive oxidative metabolism detection and acoustic assessment by using optical technique could provide more relevant information for diagnosis of voice disorders. The multi-functional vocal cords detection system could provide a good feasibility for clinical applications such as diagnosis and therapeutic monitoring of voice disorder.